A Mathematical Model for Accuracy Improvement of Determining the Radiative Characteristics of Objects on the Earth’s Surface - Azizov, B.M.; Mekhtiyev, J.S.; Mammadov, H.N.; Guliyeva, S.H. (Herald of Azerbaijan Engineering Academy, 2022)
Thermal infrared (IR) images obtained from satellites are widely used in various fields, including the study of the physical properties of the Earth’s surface, the determination of the density of water, forecasting of forest fires, observation of volcanic phenomena, as well as the allocation of geological formations with various physical and chemical properties. Due to the low resolution of satellite thermal IR scanners, the interpretation of these images is complicated by the presence of numerous physical processes and usually requires taking into account a large number of different factors. A relatively simple mathematical model is proposed for a quantitative assessment of some factors. In this article, the development of a theoretical model for analyzing the temperature distribution on the Earth’s surface is described.